Aquele que guarda: o olhar infantil sobre os anos de chumbo - Denise Ribeiro Frade (2014)
This dissertation aims to discuss texts on the Brazilian military dictatorship, which took place between 1964 and 1985. Texts of different media were chosen as the research corpus: journalistic essays, written by Zuenir Ventura, titled "1968 O que fizemos de nós" (2008), and the film "O ano em que meus pais saíram de férias" (2006), by Cao Hamburger. Our aim is to discuss the child view at the lived experiences of the Brazilian society, putting into focus the relations between fiction and history in different forms of representing the past and the reciprocal contamination between the testimonial discourse and the fictional narrative. To analyze the tension between the different types of text, we approach especially the theories of fiction and testimony. Questions concerning the memory are also involved in this dissertation since the works have memorial stories about the childhood period and the trauma generated by the parental involvement in the struggle against the military government. Thus, we reflect on the importance and specificity of the child view in the experiences arising from historical events, taking it as an alternative way of constructing knowledge about the past and convey the experience in traumatic moments.